Becoming an Agile Change Conductor - Mehta, Jade; Aalsma, Matthew C.; O'Brien, Andrew; Boyer, Tanna J.; Ahmed, Rami A.; Summanwar, Diana; Boustani, Malaz (Frontiers in Public Health, 2022)
Background It takes decades and millions of dollars for a new scientific discovery to become part of clinical practice. In 2015, the Center for Health Innovation & Implementation Science (CHIIS) launched a Professional Certificate Program in Innovation and Implementation Sciences aimed at transforming healthcare professionals into Agile Change Conductors capable of designing, implementing, and diffusing evidence-based healthcare solutions. Method In 2022, the authors surveyed alumni from the 2016–2021 cohorts of the Certificate Program as part of an educational quality improvement inquiry and to evaluate the effectiveness of the program. Results Of the 60 alumni contacted, 52 completed the survey (87% response rate) with 60% of graduates being female while 30% were an under-represented minority. On a scale from 1 to 5, the graduates agreed that the certificate benefited their careers (4.308 with a standard deviation (SD) of 0.612); expanded their professional network (4.615, SD of 0.530); and had a large impact on the effectiveness of their leadership (4.288, SD of 0.667), their change management (4.365, SD of 0.742), and their communication (4.392, SD of 0.666). Graduates claimed to use Agile Processes (Innovation, Implementation, or Diffusion), storytelling, and nudging weekly. On a scale from 0 to 10 where 10 indicates reaching a mastery, the average score for different Agile competencies ranged from 5.37 (SD of 2.80) for drafting business proposals to 7.77 (SD of 1.96) for self-awareness. For the 2020 and 2021 cohorts with existing pre and post training competency data, 22 of the 26 competencies saw a statistically significant increase. Conclusion The Graduate Certificate has been able to create a network of Agile Change Conductors competent to design, implement, and diffuse evidence-based care within the healthcare delivery system. Further improvements in building dissemination mastery and program expansion initiatives are advised.